CO30 | Joint prosthetic surgery in patients with hemophilia A: clinical-functional outcomes and quality of life (Bleeding, Thrombosis and Vascular Biology, 2025)
Background and Aims: Hemophilic arthropathy is a chronic, progressive joint disease caused by repeated hemarthroses, leading to joint degeneration, pain, stiffness, and disability. It is a major source of morbidity in patients with severe hemophilia A, significantly impairing their functional independence and quality of life. The knee, hip, and ankle are the most frequently affected joints, often requiring surgical intervention when conservative measures are no longer effective. Joint prosthetic surgery represents a crucial therapeutic option for restoring mobility and reducing pain, but it requires careful multidisciplinary planning, particularly regarding perioperative bleeding management through factor VIII (FVIII) replacement therapy. The aim of this study was to evaluate the efficacy of perioperative FVIII treatment in ensuring adequate hemostasis and to assess the clinical-functional outcomes and impact on quality of life following joint replacement in patients with hemophilia A.